Hench - Steyn, Ronan (Centre for Film and Media Studies, 2017)
Hench, by being set in the espionage genre, and following the henchman of an evil villain, offers a commentary on the modern working world by serving as a metaphor for the corporate workplace. The film follows a lowly henchman, Hank, who learns to challenge this corporate structure by achieving self-respect, thanks to an unlikely friendship with a James-Bond-esque agent. This creative explication explains how Hench achieves commentary on how large corporate structures operate to maintain control over employees, and the effects this has on individuals. It further highlights the tools and techniques used to formulate Hench into a fully realised feature screenplay.